Globalizacja i jej przeciwnicy - REWIZORSKI, Marek (Przegląd Politologiczny, 2018)
One of the results of the accelerated economic and social development over the last thirty years involves the emergence of social movements that are opposed to globalization. The objective of this paper is to present the main demands of the opponents of globalization, in particular in the context of the asymmetrical development of the parties in international relations. Anti-globalists and alter-globalists oppose the increasing importance of transnational corporations and the gradual shift of the point of gravity in the global economy from sovereign states to institutions of a regional, supraregional or global character. Anti-globalists note the progressing global crisis of legitimization of the democratic system of governance and the threat that it will be replaced by highly institutionalized technocratic structures (WTO, IMF, World Bank, European Commission). The role of anti-globalist and alter-globalist movements is of profound significance at present as they provide opposition to neoliberalism as the binding doctrine in global economy. Calling for the establishment of mechanisms that would provide for fair distribution of goods between the ‘North’ and the ‘South’ they contribute to the internationalization of the idea of collaboration between states thus ensuring that order be maintained in the global economy. Therefore, these movements support the ‘weaker party’ in international business relations – the developing countries. However, there is a negative aspect of their activity, namely they perceive globalization as a process of subordinating the weak by the strong, or – in other words – they refer to the idea of class struggle in the global economic system.